2009
DOI: 10.1111/j.1365-2567.2008.02901.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐mediated immune response to unrelated proteins and unspecific inflammation blocked by orally tolerated proteins

Abstract: Oral tolerance promotes a generalized decrease in specific immune responsiveness to proteins previously encountered via the oral route. In addition, parenteral immunization with a tolerated protein also triggers a significant reduction in the primary responsiveness to a second unrelated antigen. This is generally explained by 'innocent bystander suppression', suggesting that the transient and episodic effects of inhibitory cytokines released by contact with the tolerated antigen would block responses to the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…These and previously published results 24,[27][28][29]31 show that the exposure to tolerated antigens under immunogenic conditions has broader (general) biological and medical significance through presently undefined systemic effects that interfere with a wide array of activities, among which the regeneration of skin lesions is an important target. As the inflammatory response in the early wound is thought to be primarily innate, the idea that indirect effects of oral tolerance within the adaptive system have an impact on wound healing is highly novel.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…These and previously published results 24,[27][28][29]31 show that the exposure to tolerated antigens under immunogenic conditions has broader (general) biological and medical significance through presently undefined systemic effects that interfere with a wide array of activities, among which the regeneration of skin lesions is an important target. As the inflammatory response in the early wound is thought to be primarily innate, the idea that indirect effects of oral tolerance within the adaptive system have an impact on wound healing is highly novel.…”
Section: Discussionsupporting
confidence: 54%
“…8,14 We have shown that the indirect effects of oral tolerance triggered by the exposure to tolerated antigens block inflammatory reactions, such as those produced by carrageenan or DTH, and inhibit polymorphonuclear and mononuclear leukocyte influx into peripheral tissues. 24,28 Here, we found that the indirect effects of oral tolerance reduce the initial process of inflammation after skin lesion. The total number of inflammatory cells in the healing area of tolerant mice was lower than that in control mice (Figure 2).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Fluorescent images were acquired using the same exposure time. Myosin-specific autoantibodies were measured by indirect Elisa as previously described (61).…”
Section: Methodsmentioning
confidence: 99%
“…Food allergy is generally interpreted as a failure of oral tolerance [4]; however, there is also evidence that oral tolerance, rather than being an inhibition, promotes a stabilization of immune responsiveness [11, 12] by directly modifying inflammatory reactions [13]. We suggest that prolonged restriction and voluntary ingestion of the specific antigen by immunized animals may hinder allergic reactions and may be reached with minor digestive disturbances.…”
Section: Introductionmentioning
confidence: 99%